Membrane permeability of Prussian carp (Carassius auratus Linnaeus, 1758) spermatozoa for water and cryoprotectants molecules - Puhovkin, Anton; Mikson, Kostiantyn (нститут рибного господарства Національної академії аграрних наук України, 2020)
Purpose. Determination of permeability parameters of Prussian carp (Carassius auratus Linnaeus, 1758) spermatozoa membranes for water and cryoprotectants molecules as an important stage in the development of a protocol for their cryopreservation by vitrification. Methodology. Osmotic response of Prussian carp spermatozoa was studied using photoelectric colorimeter KF‐77 (Poland) equipped with a magnetic mixer and thermostated cuvette compartment according to our technique. To determine the permeability of plasma membranes of fish spermatozoa to cryoprotectant molecules, they were incubated in the solutions of ethyleneglycol (EG), 1,2‐ propanediol (1,2‐PD), methanol (Met) of different concentrations, or a mixture of these cryoprotectants prepared with isotonic 0.12 M NaCl aqueous solution. Permeability coefficients of spermatozoa plasma membranes for either water (Lp) or cryoprotectant (Кp) molecules were determined by fitting the experimental dependences of relative cell volumes on time and solving theoretical model equations. The activation energy (Еа) of substance transfer through cell membranes was calculated from lnLp(1/T) or lnKp(1/T), the slope of which was equal Еа/R according to the Arrhenius equation, where R was the universal gas constant. Findings. It was found that the permeability of Prussian carp spermatozoa membranes to water molecules at 20°С was 3,53±0,18  10‐14 m3/Ns, and a decrease in membrane permeability of Prussian carp spermatozoa within the range of 30–18°C was characterized by the activation energy of 48±4 kJ/mol. A decrease in membrane permeability of Prussian carp spermatozoa for cryopotectants within the range of 30–18°C was characterized by the activation energy of 82±5 kJ/mol for ethyleneglycole, 99±7 for 1,2‐propanediol and 84±6 for the mixture. This fact indicates that the molecules of the studied substances penetrate into the spermatozoon via passive diffusion through the lipid bilayer. The data obtained can be used to determine the optimal regime of spermatozoa cryopreservation for cyprinids. Originality. For the first time, the coefficients of the membranes permeability of Prussian carp spermatozoa to water molecules and cryoprotectants (ethyleneglycol, methanol, 1,2‐propanediol) and the activation energy of the these molecules transfer through the membranes were determined. Practical value. The results of the study are used in the development of media and regimes of cryopreservation of freshwater fish spermatozoa.
Keywords: spermatozoa, Prussian carp (Carassius auratus Linnaeus, 1758), membrane permeability, cryoprotectants, activation energy.